Determinants of forest owners attitudes towards wood ash recycling in Sweden - Can the nutrient cycle be closed? - Ouvrard, Benjamin; Abildtrup, Jens; Bostedt, Göran; Stenger, Anne (Ecological economics, 2019)
The use of biomass, in particular wood, has increased this last decade as a result of the European Union's objectives to reduce the use of fossil energies. This has amplified the use of whole-tree harvesting and the exploitation of forest residues from traditional timber harvest. However, these practices have some ecological consequences because they remove nutrients from the forest, thus potentially reducing soil fertility. To compensate for this nutrient loss, it has been proposed to recycle wood ash to reintroduce the exported nutrients. In this paper, we assess private forest owners' willingness to pay to spread ash in Västmanland, Sweden, where ash recycling is not widely adopted, though an increasing supply of wood ash. In particular, we take into account behavioural motives that may explain forest owners' willingness to pay (Theory of Planned Behaviour and environmental sensitivity). We conclude that Swedish forest owners generally have a positive willingness-to-pay for wood ash application in their forests, but that this measure is highly dependent on their attitudes. We also show that a forest owner's decision to apply ash to all or a portion of his/her forest is explained by two different characteristics: the landowner's environmental sensitivity and his/her perceived control of wood ash recycling.